The Impact of Ict on Teaching by Procedural Simulation - Merrou, Soumia; Berrada, Khalid; EL Kharki, Khadija; Bouhamidi, Moulay El Mehdi; Burgos, Daniel (Lecture Notes in Educational Technology, 2023)
In medicine, using simulation as a teaching method enables meeting training requirements. These requirements can be technical (gestures, procedures, decision-making) as well as non-technical (communication, collaborations, management). In fact, the different techniques used make it possible to acquire theoretical, procedural and behavioural knowledge as well as to develop clinical reasoning. The recent implementation of the bachelor–master–PhD The system has involved new requirements in terms of student nurse training and pedagogical methods used. It has created an opportunity for the integration of other methods or techniques, such as simulation in its diverse forms, at the level of Instituts Supérieurs des Professions Infirmières et Techniques de Santé au Maroc (High Institute of Nursing and Health Technology). An alarming decrease in the number of hours allotted to procedural courses—up to 75% for certain courses—represents a real threat to the quality of procedural teaching courses—even more to the use of medical simulation as a method with specific requirements. For instance, intensive care courses in anaesthesia and resuscitation for student nurses have gone down from 80 h in the old program to 20 h in the new program, which is a 75% decrease in the number of hours. Thus, in this study, we propose a new approach to teaching by simulation based on reverse pedagogical principles that stress the contribution of digital technologies and ICT in teaching and learning. A teaching model inspired by the advantages of e-learning is proposed for better time management and the active involvement of students in their learning.
Keywords: clinical reasoning; e-learning; ICT education; medical training; simulation; Scopus(2)